Price discovery between index futures and spot markets - Sifat, Imtiaz Mohamma; Mohamad, Azhar; Amin, Kevin R. (2019)
In this paper, we utilize high-frequency 15-seconds intraday data from September 2018 through to August 2019 to investigate price leadership dynamics between futures and spot markets in Malaysia. We employ Maximal Overlap Discrete Wavelet Transform to evaluate interdependence between contemporaneous futures and spot returns spaced at 15 seconds. We observe that price discovery between futures and spot markets constitutes at granular level is a scale-dependent phenomenon. Moreover, we record a counter-intuitive but not unprecedented evidence of futures market lagging the spot market in price formation with the speed of adjustment approaching convergence in between 1-8 minutes. Our findings constitute evidence against the efficient market hypothesis and hint at arbitrageable opportunities, especially by high-frequency robots. Robustness checks via BEKK-GARCH and DCC-GARCH estimations yield no contradiction.